Corporate governance and business ethics in Iceland : studies on contemporary governance and ethical dilemmas - Sigurjonsson, Throstur; Robert H. Haraldsson, 1959-; Mitchell, Jordan Paul (Emerald Publishing Limited, 2023)
Often highlighted for being a microcosm within the greater global context, Icelandic businesses and institutions provide the perfect opportunity to advance knowledge of corporate governance and business ethics amidst once-in-a-lifetime events such as the 2008 Financial Crisis and the COVID-19 pandemic. Corporate Governance and Business Ethics in Iceland provides real-world case studies of how institutions approach governance and ethics in a country where one organization's actions often have a massive ripple effect throughout the entire nation. The book offers valuable insights to businesses around the world including themes as diverse as board independence, stakeholder relations, crisis management, environmental practices, international business, marketing ethics and privacy across a wide range of industries. The combination of current case studies coupled with a practical approach to academic theory is suitable for a wide range of readers, from undergraduate students to CEOs and boards of directors. Contributing to innovative discussions surrounding Corporate Social Responsibility (CSR) and Environmental, Social and Governance (ESG) frameworks, Corporate Governance and Business Ethics in Iceland prompts sustainable and positive pathways forward.